International New Ventures from Emerging Economies: Network Connectivity and Legitimacy Building. (September 2019) - Prashantham, Shameen; Kumar, K; Bhattacharyya, Sumelika
ABSTRACT: We develop an integrative perspective on the role of coethnic ties and ties with foreign multinational enterprises (MNEs) – normally studied in isolation of each other – on the perceived legitimacy of international new ventures (INVs) from emerging economies. Building on the notions of people (interpersonal diaspora ties) and pipelines (interorganizational MNE ties) in Lorenzen and Mudambi's connectivity theory of clusters, we argue that these could contribute to the focal INV's internal and external legitimacy, respectively, as it seeks to upgrade its capabilities. We go a step further by highlighting people within pipelines – coethnic managers working in foreign MNEs – as a potentially important catalyst of the focal INV's cross-border legitimacy. Using an illustration of an INV from Bangalore, we note that India offers a fruitful setting – and one that is distinct from China – for future INV research into the role of people, pipelines and, in particular, people within pipelines. 摘要: 我们发展了一个整合的观点，解释同种族联结和与海外跨国公司的联结—在已有研究中普遍被分开考察的两种联结—对于来自新兴经济的国际新企业的合法性的作用。我们认为，Lorenzen和Mudambi的集群连接理论中的人（人际的侨民联结）和管道（组织间的跨国公司联结）的理念，可以分别有助于国际新企业在寻求提升能力过程中的内部和外部合法性。我们进一步说明管道中的人—在外国跨国公司中工作的同种族经理人—可以成为促进国际新企业跨境合法性的潜在重要人物。我们以班加罗尔的一家国际新企业为例，说明印度为未来国际新企业研究中探讨人、管道、尤其是管道中的人，提供了一种不同于中国的丰富场景。 АННОТАЦИЯ: В рамках комплексного подхода, мы изучаем общее влияние этнических связей и связей с иностранными многонациональными предприятиями (МНП), которые обычно изучаются по отдельности, на воспринимаемую легитимность интернациональных новых предприятий (ИНП) из стран с развивающейся экономикой. На основании представления о людях (межличностные связи внутри диаспоры) и системах коммуникаций (межорганизационные связи между МНП) в теории соединения кластеров Лоренцена и Мудамби, мы утверждаем, что эти связи могут способствовать соответственно внутренней и внешней легитимности ИНП, по мере того, как ИНП стремится к модернизации своих возможностей. Мы делаем еще один шаг вперед, подчеркивая роль людей в системах коммуникаций – менеджеров из одной этнической группы, которые работают в иностранных МНП, – в качестве потенциально важного катализатора трансграничной легитимности ИНП. На примере ИНП из Бангалора, мы отмечаем, что Индия представляет богатый материал, отличный от Китая, для будущих исследований по ИНП в отношении роли людей, систем коммуникаций и, в особенности, людей внутри систем коммуникаций. RESUMEN: Desarrollamos una perspectiva integral del rol de los lazos co-étnicos y los lazos con las empresas multinacionales (EMN) -normalmente estudiados de forma aislada – en la legitimidad percibida de las nuevas empresas internacionales (INV) de las economías emergentes. Sobre la base de las nociones de gente (los lazos interpersonales de la diáspora) y conductos (los lazos inter-organizacionales de las EMN) en la teoría de conectividad de clústeres de Lorenzen y Mudambi, discutimos que estos pueden contribuir a la legitimidad interna y externa de la INV central, respectivamente, dado que busca mejorar sus capacidades. Vamos un paso más allá resaltando la gente en los conductos -gerentes de la misma etnia trabajando en EMN extranjeras- como un catalizador importante de la legitimidad transfronteriza de la INV central. Usando una ilustración de una INV de Bangalore, notamos que India ofrece un entorno fructífero -y uno que es distinto de China- para futuras investigaciones sobre el papel de la gente, los conductos, y en particular, la gente en los conductos.